Benefits and Challenges in Utilizing E-Portfolio among Ucas Students’ EFLClasses in Palestine - Dawood A. Al-Hidabi; Muhammad K. Kabilan; Mahmoud D. Shakfa (BIRCU, 2020)
The widely spread usage of technology at tertiary level has stimulated professors and policymakers to search for new methods of assessment that fit the new digital generation. Therefore, the purpose of this study is to identify the benefits and challenges students get from utilizing e-portfolio in UCAS students' EFL classes. The total number of students in English Language social work classes under the humanitarian department at UCAS is 60 (30 males and 30 females). Those are officially enrolling in English Language course (DIPL 1303) at first semester of 2017/2018 academic year. A qualitative method was used to collect data for one semester. The results from the qualitative data indicated that students got four benefits from utilizing e-portfolio: Promoting feedback, improving ICT skills, enhancing quality of e-portfolio's content and holding responsibility as well as independence in the learning process. However, the students were reported to have faced some problems during implementation of e-portfolio such as: time factor, lack of efficiency and effectiveness of utilizing e-portfolio, lack of infrastructural facilities, and inability to speak English fluently. Therefore, it can be concluded that integrating e-portfolio at the tertiary level would facilitate the learning process and create a real change among the new digital generation.